Changes in the Ankle Muscles Co-Activation Pattern After 5 Years Following Total Ankle Joint Replacement - Arriagada-Tarifeno, D (Elsevier Ltd, 2018)
Background: The Hintegra® arthroplasty provides inversion-eversion stability, permits axial rotation, ankle flexion-extension, and improvements of the gait patterns are expected up to 12 months of rehabilitation. However, sensorimotor impairments are observed in ankle flexors/extensors muscles after rehabilitation, with potential negative effects on locomotion. Here we determined the timing and amplitude of co-activation of the tibialis anterior and medial gastrocnemius muscles during gait by assessing non-operated and operated legs of patients with total ankle replacement, 5 years after surgery. Methods: Twenty-nine patients (age: 58 [5.5] years, height: 156.4 [6.5] cm, body mass: 72.9 [6.5] kg, 10 men, and 19 women) that underwent Hintegra® ankle arthroplasty were included. Inclusion criteria included 5 years prosthesis survivorship. The onset and offset of muscle activation (timing), as well as the amplitude of activation, were determined during barefoot walking at self-selected speed by surface electromyography. The timing, percentage, and index of co-activation between the tibialis anterior and medial gastrocnemius were quantified and compared between non-operated and operated legs. Findings: The operated leg showed higher co-activation index and temporal overlapping between tibialis anterior and medial gastrocnemius during gait (p < 0.001). Interpretation: The neuromuscular changes developed during the process of degeneration do not appear to be restored 5 years following arthroplasty. The insertion of an ankle implant may restore anatomy and alignment but neuromuscular adaptations to degeneration are not corrected by 5 years following joint replacement. © 2018 Elsevier Ltd